ISLAMIC LITERATURE: INSTRUCTIONAL STRATEGIES IN CONTEMPORARY INDONESIA - Irwansyah, Dedi (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2019)
Although Islamic literature has gained serious attention by Islamic world since 1940s, it has not yet taken a significant place in the world literature, let alone in the English language research areas. For its opponents, Islamic literature is not yet underpinned by a solid definition, while for its proponents, Islamic literature needs further exploration in the sense of its instructional implication. This article seeks to strengthen the existence of Islamic literature by offering its theological and social grounds as well as by proposing possible instructional strategies of using the Islamic literature in teaching English within the contemporary Indonesian context. Research method including R & D and a library research were employed to collect and analyze the data. This study finds that Islamic literature has a strong theological ground and a long established social ground. It is also found that using appropriate visuals, high text exploitability, and relevant glosses are among the effective instructional strategies. Keywords: Islamic literature, English language teaching, visuals, intertextuality, glosses